2017
DOI: 10.1637/11674-051817-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Pasteurella multocida Isolates from Acute and Chronic Fowl Cholera Cases in Hungary During the Period 2005 Through 2010

Abstract: Fowl cholera (FC) is a highly contagious and economically important disease of poultry worldwide. This study was performed on 218 Pasteurella multocida isolates collected from separated breeding farms or backyards with acute and chronic FC cases in multiple localities across Hungary during the period 2005-2010. All isolates were characterized by a broad range of biochemical, serological, and molecular methods, as well as their antibiotic susceptibility to aminoglycosides (A), macrolides (M), penicillins (P), q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…In addition, inositol fermentation grouped these isolates into two biotypes such as 14 (63.64%) isolates fermented inositol, and denoted as P. multocida biotype 1, and 8 (36.36%) isolates were unable to ferment inositol, and thus denoted as P. multocida biotype 2 (Table-2). These results indicated that P. multocida might possess diverse metabolic potentials despite being identified from the same outbreak of FC, corroborating previous findings [70]. In this study, the RAPD profiling indicated less genetic heterogeneity among the studied P. multocida strains and confirmed two pathotypes of P. multocida among these 22 strains (Table-2, Figure -S2).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, inositol fermentation grouped these isolates into two biotypes such as 14 (63.64%) isolates fermented inositol, and denoted as P. multocida biotype 1, and 8 (36.36%) isolates were unable to ferment inositol, and thus denoted as P. multocida biotype 2 (Table-2). These results indicated that P. multocida might possess diverse metabolic potentials despite being identified from the same outbreak of FC, corroborating previous findings [70]. In this study, the RAPD profiling indicated less genetic heterogeneity among the studied P. multocida strains and confirmed two pathotypes of P. multocida among these 22 strains (Table-2, Figure -S2).…”
Section: Resultssupporting
confidence: 91%
“…The findings of this study demonstrated ubiquitous presence of VFGs in P. multocida, indicating their high pathogenic potentials to causing FC. The pathogenicity of P. multocida is reported to be associated with various virulence factors and the wide distribution of VAGs is significant for the survival of P. multocida in the host environment [7,9,70]. In addition, the biochemical and molecular findings of the present study corroborated with the previous findings of Omaleki et al [30].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Currently, these bacteria are divided into 5 serotypes (A, B, D, E, and F) based on capsular typing and further classified into 16 serotypes (1–16) according to the type of lipopolysaccharide (LPS); different serotypes exhibit varying degrees of virulence in animals (17). Due to the lack of effective coverage in multi-serotype vaccines, antibiotics remain the most commonly employed treatment for avian cholera despite their correlation to increased drug resistance and food safety risks of contaminating bacteria (18). Furthermore, existing live-attenuated vaccines have been observed to revert to virulent strains (19).…”
Section: Introductionmentioning
confidence: 99%
“…P. multocida causes many animal diseases, such as fowl cholera, swine atrophic rhinitis, rabbit septicemia, and bovine pneumonia ( 2 4 ). Fowl cholera, caused by avian P. multocida , is a highly contagious disease of various domestic and wild bird species, resulting in great economic losses worldwide ( 5 ). In the case of peracute or acute infection, the lung lesions dominated by hemorrhages can be characteristic of fowl cholera ( 6 ).…”
Section: Introductionmentioning
confidence: 99%